2013
DOI: 10.1097/acm.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Needs and Concerns of Senior Faculty in Academic Medicine

Abstract: Senior faculty in family medicine have significant career concerns and mentoring needs as they approach retirement, and these faculty can be valuable resources after retirement. As the age of faculty continues to rise, medical schools and specialty organizations can develop specific programs to meet the needs of these medical educators and better use this expertise in a time of limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 3 publications
2
20
0
Order By: Relevance
“…The majority of participants thought about how to remain engaged with medicine upon retirement. This is consistent with previous research that demonstrates a strong desire amongst academic physicians to continue in medicine upon retirement (Stearns et al, 2013) and speaks to the immense importance of work as both an intellectual pursuit and source of identity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of participants thought about how to remain engaged with medicine upon retirement. This is consistent with previous research that demonstrates a strong desire amongst academic physicians to continue in medicine upon retirement (Stearns et al, 2013) and speaks to the immense importance of work as both an intellectual pursuit and source of identity.…”
Section: Discussionsupporting
confidence: 90%
“…Prior research on academic physicians has primarily been limited to examining findings from survey questionnaires pointing to important concerns regarding planning and the balancing of personal and work time (Stearns, Kelly, Gjerde, Stearns, & Shore, 2013) as well as concerns about organizational injustice and ethical=moral distress within the work environment (Pololi, Krupat, Civian, Ash, & Brennan, 2012). Qualitative research of nonmedical faculty has focused on reasons for continuing to work (Dorfman, 2000) or to retire (Dorfman, 2009).…”
mentioning
confidence: 98%
“…In a systematic review of recruitment and retention interventions for underrepresented in medicine minority (URMM) faculty, Rodriguez et al reported that both mentoring and faculty development can increase retention, academic productivity, and promotion rates . In considering the mentoring needs of senior faculty, a 2012 national survey showed that 47% of senior faculty in family medicine desired a mentor and had significant mentoring needs related to career advancement, work‐life balance, maintaining health, and retirement planning …”
Section: Introductionmentioning
confidence: 99%
“…This focus may not reflect the reality of current academic medicine where mentees must learn to navigate political waters within their institution and in national organizations. Other mentorship studies have found that time must be set aside for regular mentorship to occur and that the time to do mentorship should be recognized in annual activity reviews for senior faculty 10 . Finally, mentors require formal training or coaching in order to standardize a mentorship program and ensure that mentees are receiving similar help and advice 11 .…”
Section: Discussionmentioning
confidence: 99%